Provisions And Effects Of Striking Off The Case In Accordance With The Procedures For Procedures Law No. 1 Of 2016 - الحراكي أحمد; سليمان يوسف (Latakia University Journal - Economic and Legal Sciences Series, 2021)
After issuance of legislative decree No 1 of 2016, which was a paradigm shift at law of civil procedure law. This law contained important amendments, and close the previous gaps and defects, which causing contradictory provision. After four years of practical application, appears a legal problems and shortfalls with respect to dismiss the case, so the jurisprudence had attempted to counter of this cases. This article searches of this problem regarding of signal case and pre-trial detention.